The impact of anemia within 24 h after surgery on the prognosis of patients with pseudomyxoma peritonei - Gao, Xiaoyun; Guan, Hang; Li, Yiyao; Kou, Liduo; Tian, Hua; Jia, Junhui; Bai, Wei; Bai, Yu; Di, Yanhui; Ma, Ruiqing; Wang, Xinhua (Frontiers in Oncology, 2025)
In this study, we examined the effect of postoperative anemia on the prognosis of 721 patients with pseudomyxoma peritonei (PMP). Based on the initial hemoglobin (Hb) levels measured after surgery, the patients were categorized into the normal Hb (n = 65) and anemia groups (n = 656 patients, 91%), and the anemic patients were further divided into four subgroups based on their Hb levels. Patients with normal postoperative Hb levels had a significantly higher 5-year survival rate (80%) than those with anemia (67.4%). In addition, patients with Hb levels of 81–90 g/L had the shortest median survival duration of 36.3 ± 1.4 months. Tumor recurrence rates were consistent across the groups, whereas plasma and red blood cell transfusion volumes differed among the anemia subgroups. The postoperative cytoreduction rate, peritoneal carcinomatosis index, tumor grade, and Hb level were identified as factors significantly affecting postoperative survival. In conclusion, anemia developing within 24 h after surgery significantly affects the 5-year survival rate in patients with PMP, and the severity of anemia is a crucial risk factor.